Moluscos de água-doce em estudos de ecotoxicologia: uma revisão - Santos, Fernanda Campos dos (Universidade Federal de São Carlos, 2021)
This study presents a review of the existing literature on the use of bivalves and freshwater gastropods as bioindicator animals in ecotoxicology studies. From this review, the objective was to identify the most used genera of freshwater molluscs in studies, as well as the locations and columns that appear in the largest number of publications, and the most studied classes of xenobiotics. To obtain the articles, the Web of Science (WOS) database was used, covering publications from 1945 to 2021. The biological markers used in the studies were organized into ecological, reproductive, behavioral biochemical, physiological, histological, genotoxic, exposure and morphological. A total of 553 articles were retrieved from the WOS database, and from this total, 382 works were collected. The most frequent genera of Bivalvia in the studies were identified as Corbicula, Dreissena and Anodonta, while for Gastropoda the most recurrent genera were Lymnaea, Physa and Biomphalaria. Europe is the continent with the largest number of publications on ecotoxicological tests with bivalves and freshwater gastropods; North America is the second continent on that list. For both groups, Africa is the continent with the lowest number of publications of articles on ecotoxicology. The decade with the highest number of publications worldwide was 2010, when 124 publications were recorded with bivalves, and 77 with gastropods as bioindicators. There was a tendency to collect animals in the field rather than collect them in the laboratory for use in these studies. The most used biological markers were exposure markers (57.85%), followed by biochemical markers (40.58%). The most used xenobiotics were agrochemicals, present in 71 studies.
Freshwater molluscs in ecotoxicology studies: a review
Keywords: Ecotoxicologia; Bivalves; Gastrópodes; Água-doce; Revisão; Ecotoxicolgy; Gastropod; Review; Freshwater; CIENCIAS BIOLOGICAS::ZOOLOGIA::ZOOLOGIA APLICADA::UTILIZACAO DOS ANIMAIS